Parental Partnership for Effective Educational Development of Pupils - Apostolova Nikolovska, Marija; Tomevska Ilievska, Elizabeta (Филозофски факултет, Скопје, 2020)
Studying the values is an essential, but also quite precise field for research in this time of significant socio-political and socio-economic changes – an environment that we have been living in for so long. The clash between the contemporary and the “traditional” values, i.e. their value matrices, presents a risk for research, especially among the young, who are the main movers of changes in society. The research aspect of the paper was carried out in the third cycle of the nine-year elementary education, which overlaps with the developmental period of puberty, with many changes in the emotional development of the pupils and frequent behavioural problems. The changes that occur in the educational process refer to a series of processes and results for the transformation of the educational system as a whole, but also its sub-systems, their internal transformation and changes at the school level. These changes regard changes in the organization and structure of the school, changes in the beliefs and values, changes in the behaviour, the didactic style of teaching, and above all, the cooperation and partnership with the parents for effective educational development of the pupils. Hence, the subject of this research is focused on a current and contemporary challenge in the nine-year elementary education in R. Macedonia. The subject of research is from the field of the educational component of the school.
Keywords: parental partnership, educational development, pupils